Scale-up of oxidative desulfurization for sour diesel fuel: Modeling, simulation, and reactor design using Fe/AC catalyst - Awad E. Mohammed; Wadood T. Mohammed; Saba A. Gheni (Case Studies in Chemical and Environmental Engineering)
Modeling and simulation at the bench scale are crucial for understanding industrial process behavior, particularly in oxidative desulfurization (ODS). Mathematical models are powerful tools in chemical process engineering, enabling the adjustment of process conditions without physical modifications, thereby optimizing process performance. In this study, a comprehensive mathematical model for the ODS of sour diesel fuel, supplied by the NRC refinery, was developed using O₂ as the oxidant and Fe/AC as the catalyst, based on experimental data from the literature. This model addresses key limitations of existing ODS models, including their limited applicability in industrial settings and challenges in scaling up while maintaining high sulfur conversion efficiency. By simulating an industrial batch reactor, the model advances current knowledge by providing a robust framework for scaling ODS processes. Optimal reaction conditions were determined to achieve ≥99 % sulfur conversion, with kinetic parameters of a reaction order of 1.2, an activation energy of 50 kJ/mol, and a pre-exponential factor of 9050 g(−0.2).h(−1). Scale-up results, based on these parameters, suggested optimal reactor dimensions of 1.3 m in diameter and 2 m in length. The batch reactor scale-up was conducted using the gPROMS software, yielding insights that can be applied directly to industrial reactors. Ultimately, this model contributes to the field by offering a scalable, practical approach to ODS reactor design and optimization, aiding the production of cleaner diesel fuels in compliance with stringent environmental standards.